2018
DOI: 10.1177/1461444818769689
|View full text |Cite
|
Sign up to set email alerts
|

Do tabloids poison the well of social media? Explaining democratically dysfunctional news sharing

Abstract: The use of social media for sharing political information and the status of news as an essential raw material for good citizenship are both generating increasing public concern. We add to the debates about misinformation, disinformation, and “fake news” using a new theoretical framework and a unique research design integrating survey data and analysis of observed news sharing behaviors on social media. Using a media-as-resources perspective, we theorize that there are elective affinities between tabloid news a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 28 publications
2
139
1
4
Order By: Relevance
“…Content that is outrageous and counterintuitive is thus more likely to be shared, if believed. In a survey on Twitter users who shared tabloid news during the 2017 U.K. general election, Chadwick et al (2017) found that users who were motivated by the desire to debate-to find out other people's opinions and provoke discussions-and those aiming to provoke others-by entertaining, pleasing, or upsetting them-were significantly more likely to admit sharing news that was inaccurate or exaggerated. A survey of Singapore university students by Chen et al (2015) similarly reveals that catchiness and the ability to spark conversations were key motivators for news sharing on social media.…”
Section: Viralitymentioning
confidence: 99%
“…Content that is outrageous and counterintuitive is thus more likely to be shared, if believed. In a survey on Twitter users who shared tabloid news during the 2017 U.K. general election, Chadwick et al (2017) found that users who were motivated by the desire to debate-to find out other people's opinions and provoke discussions-and those aiming to provoke others-by entertaining, pleasing, or upsetting them-were significantly more likely to admit sharing news that was inaccurate or exaggerated. A survey of Singapore university students by Chen et al (2015) similarly reveals that catchiness and the ability to spark conversations were key motivators for news sharing on social media.…”
Section: Viralitymentioning
confidence: 99%
“…Media credibility is a concept in the communication sciences that has not lost relevance for the communication research over the last decades because of constant changes in the media environment (Metzger et al, 2003, 2010, Lazer, 2018. At the practical level media credibility has significant consequences for the users (Metzger et al, 2003, P.294) and online media credibility is related by some authors to the spreading of inaccurate and biased information available online, of fake or false news or dysfunctional information (Chadwick et al, 2018).…”
Section: Source Credibility Theorymentioning
confidence: 99%
“…One side effect of those fake news and other information disorders such as partisan information or low quality journalism stained by sensationalism or editorial bias is a generalization of a disbelief in journalism and the media sphere in general (Ardèvol-Abreu & Gil de Zúñiga, 2017; Chadwick, Vaccari, & O'Loughlin, 2018).…”
Section: Information Quality: Detecting and Flagging Fake Newsmentioning
confidence: 99%